Endothelin signalling mediates experience-dependent myelination in the CNS - Swire, Matthew; Kotelevtsev, Yuri; Webb, David J; Lyons, David A; ffrench-Constant, Charles (eLife, 2019)
Experience and changes in neuronal activity can alter CNS myelination, but the signalling pathways responsible remain poorly understood. Here we define a pathway in which endothelin, signalling through the G protein-coupled receptor endothelin receptor B and PKC epsilon, regulates the number of myelin sheaths formed by individual oligodendrocytes in mouse and zebrafish. We show that this phenotype is also observed in the prefrontal cortex of mice following social isolation, and is associated with reduced expression of vascular endothelin. Additionally, we show that increasing endothelin signalling rescues this myelination defect caused by social isolation. Together, these results indicate that the vasculature responds to changes in neuronal activity associated with experience by regulating endothelin levels, which in turn affect the myelinating capacity of oligodendrocytes. This pathway may be employed to couple the metabolic support function of myelin to activity-dependent demand and also represents a novel mechanism for adaptive myelination.